Emerging Adulthood: Identity status and Parenting Styles - Justin Vianey Mercado Embalsado (Universitas Ahmad Dahlan, 2021)
The psychosocial development of emerging adults is characterized by the development of an achieved ego identity (Kroger & Marcia, 2011). This development is influenced by the parental environment (Darling & Steinberg, 1993). A one-way multivariate analysis was conducted to predict the associations between the different parenting styles (Baumrind, 1966) and identity statuses (Marcia, 1994). According to the results, there was a significant difference in the perceived parenting styles of the emerging adults ( N = 203) based on their identity status, F( 8, 392 ) = , p = 0.033; Wilk's Λ = .919, partial η2 = 0.41. To further understand the variances among the variables a discriminant analysis was conducted, which revealed that the achieved identity status lead to the variances between the parenting styles and identity status. Regardless of the perceived parenting style and socialized parental attitude an achieved identity remains to be the goal of an emerging adult's identity development.